2023
DOI: 10.3390/ani13091548
|View full text |Cite
|
Sign up to set email alerts
|

Measures of Oxidative Status Markers in Relation to Age, Sex, and Season in Sick and Healthy Captive Asian Elephants in Thailand

Abstract: Oxidative stress is a pathological condition that can have adverse effects on animal health, although little research has been conducted on wildlife species. In this study, blood was collected from captive Asian elephants for the assessment of five serum oxidative status markers (reactive oxygen species (ROS) concentrations; malondialdehyde, MDA; albumin; glutathione peroxidase, GPx; and catalase) in healthy (n = 137) and sick (n = 20) animals. Health problems consisted of weakness, puncture wounds, gastrointe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
11
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(24 citation statements)
references
References 140 publications
9
11
4
Order By: Relevance
“…For MDA, no age effect was observed, which aligns with previous research conducted on Asian elephants (14), as well as other species such as chimpanzees (57), horses (58), and humans (59). Regarding seasonal patterns, MDA concentrations remained relatively stable throughout the year except for 3 months during the rainy season (June, July, August) when lower concentrations were observed.…”
Section: Oxidant Markerssupporting
confidence: 90%
See 4 more Smart Citations
“…For MDA, no age effect was observed, which aligns with previous research conducted on Asian elephants (14), as well as other species such as chimpanzees (57), horses (58), and humans (59). Regarding seasonal patterns, MDA concentrations remained relatively stable throughout the year except for 3 months during the rainy season (June, July, August) when lower concentrations were observed.…”
Section: Oxidant Markerssupporting
confidence: 90%
“…Regarding seasonal patterns, MDA concentrations remained relatively stable throughout the year except for 3 months during the rainy season (June, July, August) when lower concentrations were observed. A previous study in elephants showed no seasonal effect on MDA based on seasonal calculations (14), and although not significant, the overall mean was higher during the summer season. Studies in Asian cattle reported higher MDA concentrations during the summer, which also had the highest THI (40,48), again demonstrating how cattle are susceptible to heat stress (56).…”
Section: Oxidant Markerscontrasting
confidence: 65%
See 3 more Smart Citations